Retrieving the doctor-patient relationship in the “language of things” of a medical history museum - Orsini, Davide (Medicina Historica, 2020)
University of Siena centuries-old tradition research and didactic is witnessed by the nowadays rich collections of museums gathered in the Sienese University Museum System (SIMUS). These elements together with the presence in Siena of one of the oldest and most innovative hospitals in Europe, represent the ideal scenario in which it is possible to carry out study experiences that in the field of Medical Humanities tend to train physicians who are aware and prepared also on aspects pertaining to the patient’s most emotional and spiritual sphere. Through the scientific assets present in its museums and the stories ‘told’ to the visitors by these instruments, the University of Siena is able to develop specific activities aimed at bringing back the practice of medicine to its original purposes: "being medicine for humans". University of Siena proposes in fact to regain, through the analysis of its cultural heritage, the observation skills and knowledge that are respectful of the human body and feelings. In this way it is possible to activate a doctor-patient dialogue that is also a kind of listening in a comparison between two different narratives, in order to arrive to a better approach not only to the disease but to the best care and assistance of the patient.